2007
DOI: 10.1186/1753-6561-1-s1-s50
|View full text |Cite
|
Sign up to set email alerts
|

Mixture modeling of microarray gene expression data

Abstract: About 28% of genes appear to have an expression pattern that follows a mixture distribution. We use first- and second-order partial correlation coefficients to identify trios and quartets of non-sex-linked genes that are highly associated and that are also mixtures. We identified 18 trio and 35 quartet mixtures and evaluated their mixture distribution concordance. Concordance was defined as the proportion of observations that simultaneously fall in the component with the higher mean or simultaneously in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 15 publications
(18 reference statements)
1
8
0
Order By: Relevance
“…Our estimate also differs greatly from the only other prevalence reported for bimodal expression in a population comprised solely of healthy persons - 28% in lymphoblastoid cells [18,28]. As the threshold for assessing bimodality in that study was much more liberal, we re-analyzed the data from this population and found only 2.9% of genes of the limited gene set previously analyzed to show bimodality consistent with the thresholds used in our analysis (see Methods).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Our estimate also differs greatly from the only other prevalence reported for bimodal expression in a population comprised solely of healthy persons - 28% in lymphoblastoid cells [18,28]. As the threshold for assessing bimodality in that study was much more liberal, we re-analyzed the data from this population and found only 2.9% of genes of the limited gene set previously analyzed to show bimodality consistent with the thresholds used in our analysis (see Methods).…”
Section: Discussionsupporting
confidence: 63%
“…Limited reports of bimodal expression patterns in other studies have also been made [ 18 - 20 ], particularly when heterogeneous tissues are being contrasted [ 21 - 26 ] such as between healthy and diseased tissue (and for which bimodal expression levels would be expected for perhaps many genes). However, in homogeneous tissue of apparently healthy individuals, such bimodality may be surprising, and hints at unrecognized heterogeneity which may involve precipitating factors of future disease development.…”
Section: Introductionmentioning
confidence: 99%
“…Gong et al [2007] reported a number of hub SNPs and hub genes. Yang et al [2007] reported six SNPs that were simultaneous predictors of gene expression levels in genes AHSA1, ELAC2, CCT3, TUBG1, and TACC3 as well as evidence of a common mixture mechanism simultaneously affecting a number of genes.…”
Section: Discussionmentioning
confidence: 97%
“…For example, Liu et al [2007] focused on two genes, one new and one from a previous paper; Yang et al [2007] selected distributions with mixtures; and Zhao et al [2007] selected multivariate normals. Given this diversity and the richness of the dataset, one might expect that the findings would have little overlap, much as the blind men of Indostan describing an elephant, where each focused on a different aspect of the elephant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation